Exome Sequencing Identifies Glycosylation Defects as a Probable Cause of Immune-Mediated Thrombotic Thrombocytopenic Purpura. (11th September 2019) - Basu, Malay Kumar; Staley, Elizabeth; Halkidis, Konstantine; Sui, Jingrui (Jean); Kocher, Nicole K; Gong, Han; Williams, Lawrence A; Marques, Marisa B; Cao, Wenjing; Zheng, X Long
Abstract: Background: Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a potentially fatal syndrome, resulting from autoantibodies against ADAMTS13. However, the mechanism underlying autoantibody formation is not known. Neither is known about the other genetic abnormality in the setting of severe deficiency of plasma ADAMTS13 activity. Methods: Whole-exome sequencing (WES) was performed in 40 patients with iTTP who had plasma ADAMTS13 activity <10% and a positive inhibitor or elevated anti-ADAMTS13 IgG. Fifteen age- and ethnicity-matched subjects who never had iTTP were recruited as healthy controls. Results: WES identified mutations in the genes involved in glycosylation, including O -linked glycosylation to be the major pathway affected in patients with iTTP. Mass spectrometry confirmed the changes in plasma levels of various glycoproteins in patients with acute iTTP when compared with those in the healthy controls. The altered glycosylation in glycoproteins may be responsible for the development of autoantibodies, susceptibility of von Willebrand factor to proteolysis by ADAMTS13, and the clearance of platelets in iTTP patients. Moreover, candidate gene analysis revealed that various genes involving in hemostasis, complement activation, platelet number and function, and inflammation were all affected in patients with iTTP, which may contribute to the onset, progress, severity, and long-term outcome of iTTP. Conclusions: Our findings provide novel insight into a pathogenic mechanism underlying autoantibody production and the potential contribution of other genetic abnormalities in pathogenesis of iTTP in the individuals with severe deficiency of plasma ADAMTS13 activity. Future Direction: Further studies are warranted to determine the specific glycosylation patterns of various plasma and cellular proteins in patients with iTTP and to determine the synergistic role of various gene mutations and severe ADAMTS13 deficiency in the pathogenesis of iTTP.